Does intensive land use decoupled from carbon emissions? an empirical study from the three grand economic zones of China - Zhang, Qingxi; Ge, Jingfeng; Liang, Yanqing; Zhang, Man; Dong, Li; Zhang, Jiazhe (Frontiers in Environmental Science, 2022)
In the context of the increasingly severe global carbon emission reduction situation, China, as the country with the largest carbon emissions in the world, how to smoothly reduce emissions without affecting economic development and the continuous improvement of people's living standards has become an important problem facing China. From the perspective of land intensive use (LIU), this paper uses standard deviation ellipse, decoupling theory, and logarithmic mean Divisia index (LMDI) model to analyze the level of LIU and carbon emissions in 30 provinces (municipalities and autonomous regions) in China, and explore ways to reduce emissions. The results show that: (1) The level of LIU in China's 30 provinces (municipalities and autonomous regions) has shown a good situation of steady progress, and the overall carbon emissions from land use have shown a slow growth trend, but the carbon emissions of some provinces (municipalities and autonomous regions) have shown a downward trend. (2) The LIU and the carbon emissions standard deviation ellipse have good spatial consistency, both of which are a north by east to south by west distribution patterns. The center of gravity of the carbon emission standard deviation ellipse moves to the northwest as a whole. (3) 63.33% of provinces (municipalities and autonomous regions) are in the ideal decoupling stage of LIU and carbon emissions. (4) According to the contribution value of the influencing factors of China's carbon emissions in descending order are energy intensity, economic scale, population scale, land use structure, energy carbon emission intensity and land scale. Actively adjusting the industrial structure and economic development mode, increasing the proportion of clean energy and energy utilization rate, controlling the speed of construction land expansion, and increasing the promotion of low-carbon emission reduction should be an important direction for future efforts.